Multicriteria time window-constrained project scheduling with applications to airport gate assignment. Part I: Methodology - Andreas Drexl; Yuri Nikulin (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 2005)
This paper addresses the airport flight gate assignment problem with multiple objectives. The objectives are to maximize the total flight gate preferences, to minimize the number of towing activities and to minimize the absolute deviation of the new gate assignment from a so-called reference schedule. The problem examined is a multicriteria multi-mode resource-constrained project scheduling problem with generalized precedence constraints or time windows. While in previous approaches the problem has been simplified to a single objective counterpart, we tackle it directly by a multicriteria metaheuristic, namely Pareto Simulated Annealing, in order to get a representative approximation of the Pareto front.
Keywords: 650; airport gate assignment; multiple criteria optimization; project scheduling; time windows; Pareto simulated annealing; Flughafen; Scheduling-Verfahren; Multikriterielle Entscheidungsanalyse; Terminplanung; Projektmanagement; Theorie